Long-term postoperative regional analgesia of the lower third of the face in patients with tumors of the oral cavity - Kushta, A.O.; Shuvalov, S.M. (Medicni Perspektivi, 2023)
Pain has a certain number of physical, psychological and social consequences. Pain is of particular importance in the postoperative period for patients with tumors of the oral cavity and of the oropharynx. The effectiveness of analgesia in the postoperative period is a serious problem in maxillofacial surgery. Postoperative pain is not always removable, sometimes it becomes chronic. Pronounced pain syndrome in the postoperative period is experienced by 40 to 75% of patients, but 50% of patients experience pain of medium and high intensity. The aim of this study was a comparative assessment of the effectiveness of a new alternative method of a long-term postoperative regional analgesia and the use of non-narcotic analgesics in patients with tumors of the oral cavity and oropharynx in the postoperative period. The study was conducted in 48 patients (38 men, 10 women, average age 58,05±12,31 years) with tumors of the oral cavity and oropharynx. Patients were divided into two groups depending on the method of postoperative analgesia. In the main group (22 patients) pain was suppressed by a long-term postoperative regional analgesia. In the control group (26 patients) analgesia was performed with non-narcotic analgesics. To control the effectiveness of analgesia, a visual analog scale was used, the duration of analgesia and the manifestation of dysphagia on the day 1, 3 and 10 after surgical intervention as well as similar effects were assessed. On the day 10 of using a long-term postoperative regional analgesia, a positive trend towards a reduction in pain syndrome was observed (2.0±0.63), in contrast to drugs of general action (p<0.05). Over the course of a long-term postoperative regional analgesia it was noted that analgesic effect increases from blockade to blockade. In 80% of patients of the main group, stage II-IVa the act of swallowing was nearly restored, only in 2 patients 2 degree of dysphagia was observed (p<0.05). The advantage of the proposed method in the adequacy and duration of analgesia was established (p<0.05), as well as a lower frequency of side effects – 9.1% and 23.3%, and restoration of act of swallowing (p<0.05). The technique of long-term postoperative regional analgesia allows reducing the invasiveness of the manipulation.